PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI METODE INKUIRI DI KELAS IV SDN 05 SUNGAI GERINGGING KABUPATEN PADANG PARIAMAN - Pedriati Pedriati (PAKAR Pendidikan, 2016)
Based on the reflection and experience in SD Negeri 05 Sungai Geringging as a teacher in class fourth, of teaching mathematics is still conventional. The students are less motivated in the following study. The researchers interested in improving mathematics learning process through the implementation of action research using the method of inquiry. This research is a classroom action research (class action research), and used a qualitative approach. This study was conducted in two cycles, carried out by collaboration between researchers and fellow teachers. The research value in the form of information about the value results obtained from the actions of observation activity teachers and students, the first test and final test of learning. Subjects in this study is the fourth grade students of SDN 05 Sungai Geringging. The research results of the first cycle the average value of 7.36 or reach students reached 59%, while the second cycle students' average score increased to 9,27 or reach students reached 86.4%. Based on the observations seen improving student learning outcomes in the learning process. It can be concluded that by using the method of inquiry can improve student learning outcomes.